Studies on comparative economic analysis of beverages and preserves of arid fruits (Indian Journal of Arid Horticulture, 2025)
This study presents a comparative economic analysis of beverages and preserves made from arid fruits, aiming to enhance the profitability of underutilized and lesser-known fruit varieties. It is evident from the results that the benefit: cost ratio from beverages was 3.93 in bael juice, 2.11 in bael squash, 2.07 in bael syrup, 2.21 ber while preserves of ber, aonla and bael have 2.76, 2.94 and 2.67, respectively. The value addition of fruits resulted in generation of income, employment as well as eliminate/ minimize malnutrition problem and post-harvest losses.